Management of perianal diseases under local anesthesia: local anesthesia in perianal diseases - Habibullah, Tarafder; Khanam Sumy, Afroza; Abu Nasser, Jamal; Akter, Fatema (Journal of the Medical College for Women & Hospital, 2024)
Background: Besides anesthetic purpose, local infiltrative/field block are commonly used for pain remission after various surgical procedure. With advances in medical science, management of various perianal disorders has been reported to be possible under local anesthesia with great ease and comfort. Aim: We performed selective perianal minor surgical procedure under local anesthesia in the form of either pudendal or subcutaneous infiltrative technique to see any procedural complications. Materials and Method: After fulfilling the inclusion and exclusion criteria a total of 50 cases were selected for this prospective study and was conducted in Enam Medical College and Hospital from January, 2022 to June 2022. Both loco-regional (pudendal block) and peri-lesional subcutaneous infiltration technique were applied. A mixture of 0.5% bupivacaine and 2% lignocaine with adrenaline was used according to body weight. All the cases were observed to see any immediate procedural complications. Follow-up was made at Outpatient Department (OPD) for at least 3 months. Results: Out of 50 cases, only 3 patients (6%) developed procedural complications and in 2 cases (4%) the procedure had failed. Conclusion: In selected proctological disorders, local anesthesia can be applied with minimum procedural complications. J Med Coll Women Hosp.2024; 20(2): 23-29